2022
DOI: 10.1002/jor.25245
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of osteoarthritis functional outcomes and intra‐articular injection volume in the rat anterior cruciate ligament transection model

Abstract: The rat surgical anterior cruciate ligament transection (ACLT) model is commonly used to investigate intra‐articular osteoarthritis (OA) therapies, and histological assessment is often the primary outcome measure. However, histological changes do not always correlate well with clinical outcomes. Therefore, this study evaluated functional outcomes in the rat surgical ACLT model and compared intra‐articular injection volumes ranging from 20 to 50 μl. Unilateral ACLT was surgically induced and static weight‐beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The results of this study indicate that larger 3D volumes and extravasation scores were noted in elbows with an IA injection of 4 mL, compared to 2 mL of contrast, regardless of whether they underwent arthroscopy. Both treatment groups that received an IA injection of 2 mL of contrast had a lower mean extravasation score of 1.55, indicating that less than 25% extravasation was noted in most elbows, which is categorized as minor similar to previous studies by Sutherland et al and Wang et al 30,31 The cadaveric study by Wang et al investigating IA injections in rat stifles also concluded that larger volumes resulted in more extravasation 31 . All post‐contrast 3D volumes were larger than the pre‐contrast 3D volumes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The results of this study indicate that larger 3D volumes and extravasation scores were noted in elbows with an IA injection of 4 mL, compared to 2 mL of contrast, regardless of whether they underwent arthroscopy. Both treatment groups that received an IA injection of 2 mL of contrast had a lower mean extravasation score of 1.55, indicating that less than 25% extravasation was noted in most elbows, which is categorized as minor similar to previous studies by Sutherland et al and Wang et al 30,31 The cadaveric study by Wang et al investigating IA injections in rat stifles also concluded that larger volumes resulted in more extravasation 31 . All post‐contrast 3D volumes were larger than the pre‐contrast 3D volumes.…”
Section: Discussionsupporting
confidence: 70%
“…The post‐contrast images were assessed for the presence of contrast within the joint, filling defects characterized by a lack of contrast present in region(s) of the joint, and the presence of contrast extravasation. Contrast extravasation on radiographs and CT images was scored by the radiologist on a scale from 0 to 4 (0 = no extravasation, 1 = < 25% contrast extravasation outside the joint, 2 = 25%–50% contrast extravasation outside the joint, 3 = 50%–75% contrast extravasation outside the joint, 4 = >75% contrast extravasation outside the joint) 30,31 …”
Section: Methodsmentioning
confidence: 99%
“…47 ACL transection resulted in impaired locomotion, mechanical allodynia, and mechanical loading loss in the early phase in animal studies. 40,46 ACLT and sham surgery decreased the weightbearing and increased the number of TRAP-positive osteoclasts in the subchondral bone as early as 1 week. 43 The activation of osteoclasts promoted proinflammatory cytokines and proteases, contributing to cartilage damage.…”
Section: Discussionmentioning
confidence: 96%
“…The OA model, induced by ACLT and MMx, involved the transection of both the anterior cruciate ligament and patellar tendon [44,58,59]. MMx was performed as previously described [60].…”
Section: Animal Oa Modelsmentioning
confidence: 99%